Religious Community Organization as Corporation: Legal Politics at the Edge of the Mine: Ormas Keagamaan Jadi Korporasi: Politik Hukum di Ujung Tambang - Nugroho, Wahyu; Syahruddin, Erwin; Anam, Saiful; Yulia, Aris (LITIGASI, 2025)
The government issued a Government Regulation on the Implementation of Mineral and Coal Mining Business Activities, which regulates the offering of Special Mining Business Permit Areas on a priority basis to business entities owned by religious community organizations. The method used is normative juridical supported by empirical data, a case approach based on developing news media. Data collection techniques through secondary data, with qualitative juridical analysis. The results of this study are first, the legal policy of granting mining business permits to religious community organizations based on the Government Regulation on the Implementation of Mining Business Activities has contradicted the Mineral and Coal Mining Law. The priority offer in the law is addressed to BUMN and BUMD, while in the government regulation it is addressed to religious community organizations, which is a constitutional problem; second, the existence of guarantees in environmental management for religious community organizations as holders of mining business permits requires compliance with these business entities with environmental management instruments. In addition, it will test the consistency of religious organizations' understanding of the concept of environmental preservation in practice or business actors carrying out mining activities.